2008
DOI: 10.1002/anie.200801885
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of QS‐21‐Xylose: Establishment of the Immunopotentiating Activity of Synthetic QS‐21 Adjuvant with a Melanoma Vaccine

Abstract: The success of antitumor and antiviral vaccines often requires the use of an adjuvant, a substance that is itself not necessarily immunogenic but significantly enhances the immune response of a patient to a coadministered antigen.[1] The adjuvant of choice in many recent immunotherapeutic advances against cancer, [2] human immunodeficiency virus, [3,4] and malaria [5,6] is the natural product saponin QS-21. [7] Extensive studies in the development of conjugate cancer vaccines demonstrated the superiority of QS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
71
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 19 publications
0
71
0
Order By: Relevance
“…Therefore, their adjuvant activity can be further modified by structural modifications such as GPI-0100 [237]. The widely used saponin-based adjuvants are Quil A, isolated from the bark of Quillaja saponaria (QS) Molina, and QS21, a more purified form, is the 21st of 22 fractions in RP-HPLC trace of semipurified QS bark extracts [238].…”
Section: Saponins and Qs21mentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, their adjuvant activity can be further modified by structural modifications such as GPI-0100 [237]. The widely used saponin-based adjuvants are Quil A, isolated from the bark of Quillaja saponaria (QS) Molina, and QS21, a more purified form, is the 21st of 22 fractions in RP-HPLC trace of semipurified QS bark extracts [238].…”
Section: Saponins and Qs21mentioning
confidence: 99%
“…They have been proven to be very effective in enhancing the immunogenicity of various vaccines, including Aβ(1-15) in mice [240]; foot-and -mouth disease virus (FMDV) antigen in mice [241]; L1 and A33 proteins in mice [242]; vaccinia virus proteins in monkeys [242]; parasitic antigens in sheeps [243]; keyhole limpet hemocyanin (KLH) conjugate antigens [238,244,245]. The effect is often toward a Th1-type response in comparison with aluminum-based vaccine such as Aβ (1-15), PADRE-Aβ(1-15)-MAP) [240], L1 and A33 proteins in mice [242], parasitic antigen (Fasciola hepatica) in sheeps [243].…”
Section: Saponins and Qs21mentioning
confidence: 99%
See 1 more Smart Citation
“…To address these challenges, our group previously achieved the first chemical synthesis of QS-21 14-15 . Subsequent studies revealed that simplified acyl chain domain variants having stable amide linkages retain adjuvant activity and exhibit decreased toxicity 16 .…”
mentioning
confidence: 99%
“…47,50 The strong anti-carrier responses can potentially interfere with the generation of glycan specific antibodies due to antigen competition. 5153 The antibodies generated against the polymer backbone were analyzed.…”
Section: Resultsmentioning
confidence: 99%